Land Cover Mapping Analysis of Paghman District Using Landsat-8 Image - Reshteen, Sediqullah; Rahmatzai, Asadullah (Journal of Natural Sciences – Kabul University, 2020)
Satellite imagery is a useful tool for analyzing the interactions between the human environment and the natural environment, aiding decision-making and planning in complex situations. Today, satellite imagery and remote sensing technologies are expanding due to the availability of high-quality data and high-accuracy analysis and applications across various sectors. Accurate classification of satellite imagery is essential for obtaining reliable information about remote sensing technology. Land cover maps are vital for natural resource studies and environmental management, as land cover changes significantly impact the earth’s surface and environment. This study's main objective was to prepare a land cover map for Paghman District using Landsat-8 satellite imagery and ERDAS software, employing both supervised and unsupervised methods.